2020
DOI: 10.3390/ani11010003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Susceptibility, Virulence and Genotyping of Campylobacter jejuni with a Special Reference to the Anti-Virulence Potential of Eugenol and Beta-Resorcylic Acid on Some Multi-Drug Resistant Isolates in Egypt

Abstract: Campylobacter jejuni is the leading cause of foodborne bacterial gastroenteritis in humans worldwide. Contaminated chickens and their products are the main sources of human campylobacteriosis. Therefore, this study aimed to detect the genotypic and virulence genes‘ profiles of multi-drug resistant (MDR) C. jejuni isolates and to assess the effects of sub-inhibitory concentrations (SICs) of eugenol and beta-resorcylic acid on the virulence of avian MDR C. jejuni isolates. These isolates were clustered together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
4
32
4
Order By: Relevance
“…(57.1%) in samples recovered from chicken and human origins at Sharkia Governorate, Egypt. This is partially similar to a previous study carried out in Poland (54.4%) [ 27 ], but the levels were higher than those obtained in previous studies carried out in Egypt; 32.8% [ 10 ], 27.3% [ 28 ] and 7.6% [ 29 ]. Herein, Campylobacter spp.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…(57.1%) in samples recovered from chicken and human origins at Sharkia Governorate, Egypt. This is partially similar to a previous study carried out in Poland (54.4%) [ 27 ], but the levels were higher than those obtained in previous studies carried out in Egypt; 32.8% [ 10 ], 27.3% [ 28 ] and 7.6% [ 29 ]. Herein, Campylobacter spp.…”
Section: Discussionsupporting
confidence: 89%
“…Among our chicken samples, Campylobacter spp. were more prevalent among cloacal swabs and liver (88.6% each), which is higher than prevalences reported in a previous study carried out in Egypt (54.3% and 34.1%, respectively) [ 10 ]. In the current study, chicken franks and luncheon meats were Campylobacter negative (0% each), which is in complete agreement with a previous study conducted in Egypt [ 31 ].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…It has a similar or higher discriminatory power than MLST, especially in short-term and localized epidemiological investigations [58][59][60][61]. Punctual studies from multiple places worldwide have reported a high prevalence of flagellin A and B in C. jejuni [62][63][64][65][66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%